The Femoral Intercondylar Notch During Life: An Anatomic Redefinition With Patterns Predisposing to Cruciate Ligament Impingement - Hirtler, Lena; Röhrich, Sebastian; Kainberger, Franz (American journal of roentgenology (1976), 2016)
The goals of this study were to test whether age- and sex-dependent variations in the size and shape of the intercondylar notch exist and to define the landmarks and measurements best suited for assessment of the intercondylar notch on MR images. In this retrospective cross-sectional study, 329 patients were divided into six age groups, and their MR images (3-T coronal T2-weighted fat-suppressed spectral attenuated inversion recovery [SPAIR], sagittal proton density-weighted, axial T2-weighted fat-suppressed SPAIR) were evaluated. The intercondylar notch was measured and its shape evaluated on coronal images. Three shapes of intercondylar notch were defined. The intercondylar notch is subject to change throughout life, narrowing more distally and widening more proximally. Its width ranges from 16.23 ± 2.71 mm before the age of 11 years to 19.38 ± 2.90 mm in middle age and then decreases to 18.6 ± 2.36 mm after the age of 60 years. Its shape changes from an A shape in the early stages of life to an Ω shape in the later stages. The term "intercondylar space" is introduced as a morphologic description of the osseous intercondylar notch and adjacent structures. The femur as a whole is subject to substantial plastic deformation throughout life, not only in its proximal part, with respect to torsion, but also in its distal extent.